MELK prevents radiofrequency ablation-induced immunogenic cell death and antitumor immune response by stabilizing FABP5 in hepatocellular malignancies - Bu-Fu Tang; Wang-Ting Xu; Shi-Ji Fang; Jin-Yu Zhu; Rong-Fang Qiu; Lin Shen; Yang Yang; Qiao-You Weng; Ya-Jie Wang; Jia-Yi Ding; Xiao-Jie Zhang; Wei-Qian Chen; et al. (Military Medical Research)
Abstract Background Radiofrequency ablation (RFA) is an efficient treatment with unlimited potential for liver cancer that can effectively reduce patient mortality. Understanding the biological process related with RFA treatment is important for improving treatment strategy. This study aimed to identify the critical targets for regulating the efficacy of RFA. Methods The RFA treatment in hepatocellular carcinoma (HCC) tumor models in vivo, was analyzed by RNA sequencing technology. The heat treatment in vitro for HCC tumor cells was also constructed to explore the mechanism after RFA treatment in tumor cells. Nanoparticles with high affinity to tumor cells were applied as a new therapy to interfere with the expression of maternal embryonic leucine zipper kinase (MELK). Results It was found that RFA treatment upregulated MELK expression, and MELK inhibition promoted RFA efficacy by immunogenic cell death and the antitumor response, including anti-tumoral macrophage polarization and increased CD8+ T cell cytotoxicity in HCC. Mechanically, MELK binds to fatty acid-binding protein 5 (FABP5), and affects its ubiquitination through the K48R pathway to increase its stability, thereby activating protein kinase B (Akt)/mammalian target of rapamycin (mTOR) signaling axis to weaken the RFA-mediated antitumor effect. In addition, the synthesis of arginylglycylaspartic acid (RGD)-lipid nanoparticles (LNPs) targeting tumor cell-intrinsic MELK enhanced RFA efficacy in HCC. Conclusion MELK is a therapeutic target by regulating RFA efficacy in HCC, and targeting MELK via RGD-LNPs provides new insight into improving RFA efficacy in HCC clinical treatment and combating the malignant progression of liver cancer.